Oxipropilação total e parcial de resíduos lignocelulósicos e oxipropilação parcial de celulose bacteriana para produção de polióis e obtenção de material bifásico monocomponente - Rosa, Joyce Rover (2014)
This research aims at both total and partial oxypropylation of lignocellulosic residues found in the Brazilian city of Uberlândia-MG, such as: mango pit, soybean skin, sugar cane straw, corn straw, corncob and from bacterial cellulose as well, in order to obtain two products: i) a viscous polyol; and ii) a fibrous solid residue superficially modified by grafting a thermoplastic polymer layer poly(propylene oxide). The raw materials, as well as the oxypropylated products obtained, were characterized after being submitted to several techniques, such as: X-Rays Diffraction, Infrared Spectroscopy under Fourier Transform, Thermogravimetric analyses, Scanning Electron Microscopy, Content of Solid residue superficially modified, Content of Homopolymer of propylene Oxide, Hydroxyl Index and Viscosity. In order to obtain a viscous polyol from sugar cane straw, it is indicated: 15 ml of propylene oxide in temperature of 200 °C, because this condition showed the lowest content of solid residue superficially modified, and indicated better results during the conversion of the raw material tested. After both total and partial oxypropylation of lignocellulosic residues we could obtain: i) both polyol compound poly(propylene oxide) and molecules from this lignocellulosic residue (cellulose, lignin and polyoses); ii) a solid residue fibrous superficially modified by grafting a thermoplastic polymer layer of poly (propylene oxide), also verified during the partial oxypropylation of bacterial cellulose. The results of thermogravimetry, Spectroscopy in Infrared and X-Ray Diffraction, in addition to Scanning Electron Microscopy pictures harmonized themselves and confirmed the presence of a thermoplastic superficial layer in the cellulose fibers from the residues and bacterial cellulose superficially modified by partial oxypropylation . The materials developed in this study can be converted into high added value products of industrial interest such as obtaining a self-reinforced composite as well as rigid polyurethane foams. Moreover, the oxypropylation can be an alternative to enlarge the range of applications of these renewable sources. In addition, it can also contribute to green Chemistry for it represents a simple process and does not generate by-products: all the material inserted into the reactor is converted into the desired final product.